PENGARUH PENDIDIKAN, SKALA USAHA, MASA MEMIMPIN DAN UMUR USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI (STUDI EMPIRIS PADA UMKM KOTA PEKANBARU) - Akbar Radeka; Kennedy Kennedy; Natariasari Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this research was to identify and analyze about (1) The influence of owner’s education on the use of accounting information (2) The influence of business scale on the use of accounting information (3) The influence of lead time on the use of accounting information and (4) The influence of business age on the use of accounting information. Population in this research is MSMES in Pekanbaru district. The method that used to the sample selection was purposive sampling method. The number of samples in this research were 86 respondents. The type of data used in this study is primary data. Data collection techniques used survey techniques by distributing questionnaires. Data analysis techniques used in this research was multiple linear regression analysis using Statistical Product and Service Solution (SPSS) version 23.0 for Windows as data processing software program. Results of hypothesis test using statistical t-test showed the significant value of owner’s education variable 0.000> 0.05, which means that H1 is accepted, the scale business variable 0.000 < 0.05, which means that H2 is accepted, lead time variable 0.029 < 0.05, which means the H3 is accepted, and age business variables 0.039 > 0.05 which means that H4 is accepted. The results showed that owner’s education, business scale, lead time, and business age has effect on the use of accounting information.Keywords: Owner’s Education , Business Scale, Lead Time, Business Age, and The Use of Accounting Information